Stress induced ordering due interstitials in Nb-4.7 at.%Ta - de Almeida, L. H.; Grandini, Carlos Roberto [UNESP]; Machado, JPB; Rodrigues, D. (Elsevier B.V., 2005)
The presence of interstitial elements in metals cause strong changes in their physical, chemical or mechanical properties. These interstitial impurities interact with the metallic matrix atoms by a relaxation process known as stress induced ordering. Relaxation processes give rise to a peak in the internal friction spectrum, known as Snock effect. The presence of substitutional solutes has a strong influence on Snoek effect, particularly if the substitutional solute element is the one, which interacts with the interstitial element. Anelastic spectroscopy measurements provide information of the behavior of these impurities in the metallic matrix. In this paper, polycrystalline samples of Nb-4.7 at.%Ta alloy have been analyzed in the as-received condition. Measurements of anelastic spectroscopy were carried out using an inverted torsion pendulum, operating with frequency of 2.0-30.0 Hz and in a temperature range between 300 and 700 K. It was observed the presence of a relaxation structure that have been attributed to stress induced ordering due to interstitial atoms around atoms of the metallic matrix. The relaxation structure have been decomposed in its constituent peaks, what it allowed to identify the following relaxation processes: Ta-O, Nb-O and Nb-N. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: internal friction; anelastic spectroscopy; gases in metals; Nb-Ta alloys